CoALM, a Model of Autonomous Learning Approach for the ETL in the Travel Industry Study Program of UHN IGBS Denpasar-Bali-Indonesia - Ratni, Ni Putu; Dollah, Syarifuddin; Basri, Muhammad; Sakkir, Geminastiti (Celebes Journal of Language Studies, 2025)
This research was motivated by the lack of references regarding the implementation of the Autonomous Learning Approach in English teaching and learning (ETL) for the Travel Industry Study Program at UHN IGBS Denpasar. The purpose of this study was to explore the implementation of the Collaborative Autonomous Learning Model (CoALM), which emerged from the execution of the Autonomous Learning Approach in ETL for students in the Travel Industry Study Program of UHN IGBS Denpasar; the research utilized a qualitative approach, employing grounded theory methods and data triangulation analysis; the findings indicated that the students' efforts to implement Autonomous Learning in their English practice and studies led to the development of a collaborative learning environment. This collaboration arose from the students' engagement in practical language application within the field. It represented a natural form of autonomous language learning that yielded mutual benefits for both students and foreign tourists, ultimately resulting in the creation of the Collaborative Autonomous Learning Model (CoALM), which is student-directed; the research findings were analyzed and concluded based on data collected from various sources and locations, which presented certain constraints. Therefore, it is suggested that future researchers explore this area of study using a broader range of data sources and locations.